2004
DOI: 10.1016/j.jedc.2003.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Network structure and the diffusion of knowledge

Abstract: This paper models knowledge di usion as a barter process in which agents exchange di erent types of knowledge. This is intended to capture the observed practice of informal knowledge trading. Agents are located on a network and are directly connected with a small number of other agents. Agents repeatedly meet those with whom direct connections exist and trade if mutually proÿtable trades exist. In this way knowledge di uses throughout the economy. We examine the relationship between network architecture and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
483
3
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 757 publications
(543 citation statements)
references
References 39 publications
10
483
3
11
Order By: Relevance
“…Geographical and technological proximity may induce a process of knowledge diffusion that does not depend directly on economic agents' decisions. In the case of intended spillovers, knowledge flows across a-spatial networks where agents exchange ideas on a voluntary base thanks to formal or informal agreements (Cowan and Jonard, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Geographical and technological proximity may induce a process of knowledge diffusion that does not depend directly on economic agents' decisions. In the case of intended spillovers, knowledge flows across a-spatial networks where agents exchange ideas on a voluntary base thanks to formal or informal agreements (Cowan and Jonard, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, more centralized networks are also more vulnerable, since their dependence on the functioning of single actors is higher as compared to other network structures. With respect to the rate of knowledge diffusion, Cowan & Jonard (2004) could show that small world structures are the superior form of organization. The results of Schilling & Phelps (2007) on the structure of industry networks add to the difficulties in evaluating this development towards increased centralization.…”
Section: Resultsmentioning
confidence: 99%
“…Cowan (2004) examined the relationship between network structure and diffusion performance, and concluded that knowledge diffusion in small-world networks with different structure properties have great difference [9]. These studies have used simulation to explore knowledge diffusion process, but did not analyze the impact of such knowledge diffusion on the overall economy of high-tech innovation networks.…”
Section: Introductionmentioning
confidence: 99%